The Influence of Trauma on End-of-Life Decision-Making - Nortjé, Maya; Pontarelli, Maureen; Doherty, Ian; Terrell, Karen; Robles, Carla; Nortjé, Nico (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2026)
This case study illustrates how principles and approaches from trauma-informed care can be used in a setting where a family is requesting the medical team not to share bad news out of fear of re-traumatization. A trauma-informed ethics consultation acknowledges how unresolved trauma may obstruct open and ethical communication. Effective facilitation of ethical dialogue is only possible once underlying trauma affecting communication is acknowledged and addressed.